Should gains from criminal knowledge be forfeited? - Mamak, Kamil (Crime, law and social change, 2022)
Nobody should profit from crime; this fundamental moral principle is uncontroversial. At the level of public declaration, few people are likely to disagree with this statement; however, controversies arise when the implementation of this principle is under discussion. Numerous provisions exist that aim to strip criminals of the proceeds from their crimes, but not all aspects of this issue are immediately apparent. For example, a significant question is how to treat profits that a criminal makes from activities including recounting stories about their criminal activities, publishing books describing their actions, or creating YouTube videos presenting details about their crimes. Such profits are either treated as legitimate or are targeted by complicated legal methods of deprivation. The view presented in this paper could facilitate the ability to strip criminals from these forms of profit. This article argues that revenue accruing from knowledge gained from association with crime should be treated as indirect proceeds of crime and, as such, should be forfeited.